COUNSELING GUIDANCE IN THE PERSPECTIVE CHANGE OF STUDENT'S MORAL AND BEHAVIOR IN SCHOOL - Suid Saidi (Universitas Muhammadiyah Ponorogo, 2022)
This research aims to find out significantly about the benefits of guidance to students by conducting direct interviews with students who have received counseling guidance, so that the authors can measure the level of benefits for the students concerned. that is a case that exists in the community, so that they can directly know, measure the extent of the benefits. After conducting a comprehensive study of 10 students as participants and informants, the author sees that there are still some things that need to be improved, so that the guidance service system can run. in accordance with the expected results, the conclusions are similar to the findings in this study, that this guidance section in addition to needing improvement also needs attention from the government, and community participation (parents), so that the results of the guidance are able to create a better discipline. for students